The exclusion of the body in Sein und Zeit and the denial of a phenomenology of the body in Heidegger’s thought - Johnson, Felipe (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
Through a reflection on the lack of a detailed thematization of the human body in Sein und Zeit and, considering the denial of a «phenomenology of the body» in Zollikoner Seminare, this paper aims to develop the methodical advice behind Heidegger’s treatment of human corporality. In this context, we will emphasize the incompatibility between the kind of being of Dasein and the kind of being that make up the traditional interpretation of the body: the body as a thing. Based on the foregoing, this study will discuss on the necessity to concentrate the attention on the ontological belonging of the body to the being of human being by the attempt to deploy an existential consideration of human corporality.
Keywords: human body; phenomenology; Vorhandensein; Dasein; Heidegger